Turning back to God Hosea and Obadiah simply explained - Bentley, Michael (Durham, UK Evangelical press, 2000)
Includes bibliographical references.
Keywords: Bible. O.T. Hosea -- commentaries; Bible. O.T. Obadiah -- commentaries